(3GdNWhGJ GdELQGFjI h GddhLSJjI ddJOQjH GdGOGQj (B/s - (3GdeYQGL, SejQ YWjg s ((3OShb (B;(3GdLRGFQ (B:s (3OGQ GdYde hGdGjeGf (B;(3OGQ GdLOjO ddfTQ h GdJhRjY ,s, 2020)
(3cJGH (B"(3GdNWhGJ GdELQGFjI h GddhLSJjI ddJOQjH GdEOGQj(B" (3eDdag gh GdOcJhQ SejQ YWqjg GdeYQGL, hjbOe GdcJGH OdjdkG Mhd cjajI hVY hEOGQI YedjGJ GdJOQjH GdEOGQj ef GdfhGMj GdJfajPjI hGdafjI, HGdEVGaI Edi GdNWhGJ GdYedjI dJNWjW hJfXje hJfajP GdHQGeL GdJOQjHjI HaYGdjI dVeGf fLGMgG hJMbjb CgOGagGs
Keywords: (3GdELQGFjI s; (3GdJOQjH GdGOGQj s; (3GddhLSJjIs